-15k+19=9

Subtract 19 from both sides of the equation.

-15k=9-19

Subtract 19 from 9.

-15k=-10

-15k=-10

Divide each term in -15k=-10 by -15.

-15k-15=-10-15

Cancel the common factor of -15.

Cancel the common factor.

-15k-15=-10-15

Divide k by 1.

k=-10-15

k=-10-15

Cancel the common factor of -10 and -15.

Factor -5 out of -10.

k=-5(2)-15

Cancel the common factors.

Factor -5 out of -15.

k=-5⋅2-5⋅3

Cancel the common factor.

k=-5⋅2-5⋅3

Rewrite the expression.

k=23

k=23

k=23

k=23

The result can be shown in multiple forms.

Exact Form:

k=23

Decimal Form:

k=0.6‾

Solve for k -15k+19=9